Dasein online! a study of the experience of flow in the virtual playground - Godley, Donnae-Maree (Rhodes University, Faculty of Humanities, Department of Psychology, 2012)
The purpose of this study was twofold. First, it aimed to present and understand the experiences of online gamers from the paradigm of positive psychology. To achieve this, the phenomenon of flow was investigated to see whether or not, it is experienced whilst gaming online and if present, how it is revealed in this context. The second purpose was to contribute to theory building and to respond to extant research recommendations. Aligned with a qualitative orientation, the method selected to achieve the objectives of the study was interpretative phenomenological analysis. A sample of four participants who met the criteria for inclusion in the research were selected and interviewed using semi-structured interviews. Data was analysed and interpreted inductively and categorised into superordinate themes. These were presented as two sections: Section A explored the experience and meaning of online gaming through the following three superordinate themes; intention, pre-gaming rituals and gaming process. Section B discussed the social experience and meaning of gaming online through the superordinate theme, a gamers way. This study both challenged and supported theory and research in the field and introduced novel areas, such as pregaming rituals and the subthemes; marijuana and gaming space. This is a notable and promising "side effect" of a research design that is exploratory. Findings called for future multi-disciplinary research into flow, gaming and online relationships considering Csikszentimaihalyi"Ÿs concept of autotelic relationships and Heideggers"Ÿ philosophical framework.
Keywords: Internet games -- Social aspects -- Research; Virtual reality -- Social aspects -- Research; Fantasy games -- Social aspects -- Research; Human-computer interaction -- Research; Online identities